A Noble in Harput: Çötelizâde Hacı Mehmed Efendi - Çelik, Kürşat (Fırat University, 2020)
In the 18th century, in order to eliminate the financial distress that arose with the weakening of the Ottoman Empire, “the Mukâtaas”, whose income belonged to the state, İltizam was started to be given with the condition of “Kayd-ı Hayat”(lifetime) with a procedure called “Mâlikâne”. These were taken by the wealthy elite and civil servants in the local community, and a clan or group that appeared as a “Ayan”. With the weakening of the central administration, the “Ayan” in the provinces became an administrative power as well as their economic power and were effective in the provincial administration. In this study, the financial resources of Çötelizâde Hacı Mehmet Efendi, who is one of the Harput Ayan’s, his relations with local administrators and his role in the events around Harput were studied. With this research, it has been revealed that the murder of Çötelizâde Hacı Mehmed Efendi is an example of the power and power struggle that occurred between Ayan and local administrators in the provinces. Also the foundation works of Çötelizâde Hacı Mehmed Efendi were examined.

18. yüzyılda Osmanlı Devleti’nin zayıflamasıyla birlikte ortaya çıkan mali sıkıntıyı gidermek için geliri devlete ait olan mukâtaaların mâlikâne adı verilen bir usul ile kayd-ı hayat şartıyla iltizama verilmeye başlanmıştır. Bunları yereldeki zengin seçkinler ile devlet memurları almış ve âyan olarak ifade edilen bir zümre veya grup ortaya çıkmıştı. Merkezi idarenin zayıflamasıyla birlikte taşradaki âyanlar iktisadî güçlerinin yanı sıra idarî olarakta bir güç olmuşlar ve taşra yönetiminde etkili olmuşlardır. Bu çalışmada, Harput âyanlarından Çötelizâde Hacı Mehmed Efendi’nin âyanlığının maddi kaynakları, yerel idarecilerle olan ilişkileri Harput ve çevresinde meydana gelen olaylardaki rolü araştırılmıştır. Yine bu araştırma ile Çötelizâde Hacı Mehmed Efendi’nin katl edilme sürecinde yaşanan olayların taşradaki âyan ve yerel idareciler arasında meydana gelen güç ve iktidar çekişmesinin bir örneği olduğu ortaya çıkarılmıştır. Yine bu makalede Çötelizâde Hacı Mehmed Efendi’nin vakıf eserleri incelenmiştir.
HARPUTLU BİR ÂYAN: ÇÖTELİZÂDE HACI MEHMED EFENDİ